2013
DOI: 10.1371/journal.pone.0065006
|View full text |Cite
|
Sign up to set email alerts
|

Oral Perceptions of Fat and Taste Stimuli Are Modulated by Affect and Mood Induction

Abstract: This study examined the impact of three clinical psychological variables (non-pathological levels of depression and anxiety, as well as experimentally manipulated mood) on fat and taste perception in healthy subjects. After a baseline orosensory evaluation, ‘sad’, ‘happy’ and ‘neutral’ video clips were presented to induce corresponding moods in eighty participants. Following mood manipulation, subjects rated five different oral stimuli, appearing sweet, umami, sour, bitter, fatty, which were delivered at five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…This is in line with previous research suggesting that basic tastes can be influenced by changes in affect and stress (Ileri-Gurel et al, 2012;Platte et al, 2013). Significantly, our study revealed that affective manipulations impact the taste system in an observational field study, demonstrating its applicability in a real-world setting, as opposed to previous work within a laboratory setting.…”
Section: Perceived Taste Intensity Varies With Emotional Statesupporting
confidence: 91%
See 2 more Smart Citations
“…This is in line with previous research suggesting that basic tastes can be influenced by changes in affect and stress (Ileri-Gurel et al, 2012;Platte et al, 2013). Significantly, our study revealed that affective manipulations impact the taste system in an observational field study, demonstrating its applicability in a real-world setting, as opposed to previous work within a laboratory setting.…”
Section: Perceived Taste Intensity Varies With Emotional Statesupporting
confidence: 91%
“…In agreement of our findings, Heath et al (2006) demonstrated that elevated levels of serotonin (attributed to feelings of wellbeing and happiness) are associated with enhanced sweet acuity, while elevated levels of the stress hormone noradrenaline result in increased sour perception. Furthermore, previous studies have showed that mild stressors or negative affect correspond with lower intensity ratings of sweet stimuli (Al'absi et al, 2012;Dess & Edelheit, 1998) and that mood manipulations are associated with a variation in the perceived intensity of sourness (Platte et al, 2013). Importantly, the results of our study expand upon the conclusions of the aforementioned studies, indicating sour and sweet intensity perception are two dimensional: in addition to the effects seen with negative affect, there is a contrary relationship with positive affect.…”
Section: Perceived Taste Intensity Varies With Emotional Statesupporting
confidence: 83%
See 1 more Smart Citation
“…Using the State-Trait Anxiety Inventory (STAI), we determined state (current anxiety induced by a situation) and trait (global and enduring) anxiety scores of all participants. Trait anxiety has been shown to affect eating behavior in both lean and obese subjects as well as influence ratings of sweet and bitter flavors, but other studies indicate that state anxiety predicts increased food intake (7, 8, 20, 21). We therefore studied each component of anxiety separately, stratifying our analyses by sex.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors influencing taste have been reported such as olfaction, hearing, tactility, aging, and stress [27] [29], although visual factors have been reported as having the strongest effect on the taste of food and meals [30] [31]. Petra Platte and colleagues report that after seeing negative or positive images, the intensity of sweetness and acidity changes [32]. It is assumed that the change of the threshold value was not detected because the content of the remarks, not the visual stimulus, was changed and the measurement of taste comprised the electric taste threshold instead of the five basic tastes.…”
Section: Discussionmentioning
confidence: 99%